Self-managed working time and employee effort: Microeconometric evidence - Michael Beckmann; Thomas Cornelissen (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
Based on German individual-level panel data, this paper empirically examines the impact of self-managed working time (SMWT) on employee effort. Theoretically, workers may respond positively or negatively to having control over their own working hours, depending on whether SMWT increases work morale, induces reciprocal work intensification, or encourages employee shirking. We find that SMWT employees exert higher effort levels than employees with fixed working hours, but after accounting for observed and unobserved characteristics and for endogeneity, there remains only a modest positive effect. This effect is mainly driven by employees who have a strong work ethic, suggesting that intrinsic motivation is complementary to SMWT. Moreover, reciprocal work intensification does not seem to be an important channel of providing extra effort. Finally, we find no SMWT effect among women with children in need of parental care indicating that these workers primarily choose SMWT to accommodate family obligations.
Keywords: J24; J81; M50; 330; self-managed working time; employee effort; reciprocity; work ethic; intrinsic motivation; family obligations; complementarity